Effects of retirement on cognitive functioning: Evidence from biomedical and administrative insurance claims data - Henrik Bergschneider; Robin Kottmann; Hendrik Schmitz; Matthias Westphal (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We study the effects of retirement on cognitive functioning among women aged 63 to 67 by exploiting a German retirement reform that raised the early retirement age for women born after 1951 by three years, from 60 to 63. Our indicators of cognitive functioning are experimental measures (word recall, semantic fluency, and the Stroop test) from a large biomedical data set, as well as the diagnosis of cognitive disorders from administrative health insurance claims. We find reductions of around 12% of a standard deviation per year in retirement for measures of fluid intelligence and of an insignificant 6% for crystallized intelligence. The diagnosis of cognitive disorders remains unaffected. – – Wir untersuchen die Auswirkungen des Ruhestands auf die kognitiven Fähigkeiten von Frauen im Alter von 63 bis 67 Jahren, indem wir eine deutsche Rentenreform nutzen, die das Frührenteneintrittsalter für Frauen, die nach 1951 geboren wurden, um drei Jahre, von 60 auf 63 Jahre, anhob. Unsere Indikatoren für die kognitive Leistungsfähigkeit sind experimentelle Messwerte (Tests zu Worterinnerung, semantischer Wortflüssigkeit und zum Stroop Effekt) aus einem großen biomedizinischen Datensatz sowie die Diagnose kognitiver Erkrankungen aus administrativen Krankenversicherungsdaten. Als Ergebnis finden wir eine Reduktion von etwa 12% einer Standardabweichung pro Jahr im Ruhestand für Maße der fluiden Intelligenz und eine insignifikante Reduktion von 6% für kristalline Intelligenz. Die Diagnose von kognitiven Erkrankungen bleibt davon unberührt.
Keywords: C31; J14; J24; 330; Cognitive abilities; retirement; pension reform